Impact of Victimization in the Lives of Incarcerated Women in South Carolina, 2000-2002 - DeHart, Dana ([Verlag nicht ermittelbar], 2007)
This study examined victimization in the lives of incarcerated women, specifically victimization as a risk factor for crime, with particular emphasis on the direct and indirect ways in which the impact of victimization contributed to criminal involvement. Interviews were conducted with 60 women incarcerated in a maximum security state correctional facility in South Carolina from October 2001 to August 2002. Interview measures consisted of participant responses to loosely-structured open-ended prompts and addressed each woman's own perspective on psychological, physical, and sexual victimization within her life, as well as her history of family and peer relationships, alcohol and drug use, and criminal activity. The South Carolina Department of Corrections (SCDC) provided demographic and criminal history information for each prospective participant, including participants, no-shows, and decliners (Part 1) and for the female prison population without the prospective participants (Part 2). These data were used for sampling decisions and provide descriptive information on sample characteristics. In addition the SCDC provided inmate data on offenses committed while in the SCDC (Part 3), disciplinary actions at the SCDC (Part 4), education through the SCDC (Part 5), and known prior offenses (Part 6). The project also conducted online searches in NewsLibrary for media reports concerning women who participated in the study. Variables include age, race, number of children, marital status, criminal offense history, correctional disciplinary records, probation/parole information, victim/witness notification, corrections program participation, intelligence scores, math and reading scores, basic academic history/degrees, mental health assessment, and special medical needs.